Physicochemical and thermal characterization of hydroxyethyl cellulose - wheat starch based films incorporated thymol intended for active packaging - Nozieana Khairuddin,; Ida Idayu Muhamad,; Wan Aizan Wan Abd Rahman,; Bazlul Mobin Siddique, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Biodegradable packing materials with antimicrobial properties have been a concern for years because of its positive environmental implications. The present work aimed to develop the formulation of hydroxyethyl cellulose (HEC)/wheat-starch based film in which the active compound, thymol (0.5, 1, 1.5, 2, and 2.5% w/w) were incorporated into the polymeric material. Solution casting method was used for the film preparation while thymol was incorporated prior to casting. The physical and chemical properties of the developed film were determined. SEM was found to have a smooth and homogeneous with a small amount of thymol which grows coarser with 1.5% or higher thymol content. FTIR was used to find the chemical property of the film and suggested that the carbonyl functional group was unchanged in the film, however, -OH groups increased substantially with increased amount of thymol. Thermal properties were profiled through thermogravimetric analysis and differential scanning calorimeter where the AM film containing 1.5% (w/v) of thymol shows the highest thermal stability and decomposes less in comparison to other samples. The inhibitory capability of the film was tested against a list of microbial contamination and was found to successfully inhibit the growth of selected gram positive and gram negative bacteria in a wide range of studied concentration. The mechanical properties of the films were improved by 60.3% with an optimum tensile strength at thymol concentration of 1.5% w/w. It can be concluded that the film properties are retained chemically whereas mechanical properties, strength, flexibility and function of the film are being enhanced remarkably by the incorporation of thymol.